Performance Analysis of Islamic Banks Listed on the Indonesia Stock Exchange (IDX) Based on the Risk Based Bank Rating (RBBR) Method for the 2020-2023 Period - Syahputra, Yusuf Candra; Widodo, Moch. Wahyu (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research objective: The aim of this research is to assess and examine the financial performance of Islamic banks registered on the Indonesia Stock Exchangeing (IDX) by utilizing the Risk Based on Bank Rating (RBBR) approach during the 2020-2023 timeframe. Desighn/Methode/Approaach: This research adopts a quantitative method with a descriptive approach. The study focuses on Islamic banks listed on the Indonesia Stock Exchange (IDX), including Bank Aladin Syariah, Bank Syariah Indonesia, Bank BTPN Syariah, and Bank Panin Dubai Syariah. To gather data, the documentation technique is employed, where relevant financial information is collected from the official websites of the IDX and the respective banks. The analysis in this study evaluates the performance of Islamic banks using the Risk-Based Bank Rating (RBBR) method as a key framework. Research Findings: The findings of this research present an evaluation of the financial performance of Islamic banks registered on the Indonesia Stock Exchange (IDX) from 2020 to 2023 using the Risk-Based Bank Rating (RBBR) approach. Among the banks analyzed, PT Bank Aladin Syariah Tbk exhibited notable fluctuations in its performance, with its strongest financial results recorded in 2020. These variations indicate changes in the bank's financial stability over the years, influenced by various internal and external factors.and the biggest challenges in 2022, but managed to start recovery in 2023. PT Bank Syariah Indonesia Tbk showed high stability with a "Very Healthy" status for four consecutive years, reflecting consistent risk management and operational efficiency. PT Bank BTPN Syariah Tbk maintained a "Very Healthy" composite rating every year, with strong financial performance despite increased risks in 2023. Meanwhile, PT Bank Panin Dubai Syariah Tbk showed significant performance improvements from the less healthy category in 2020-2021 to very healthy in 2022-2023, with challenges in operational efficiency remaining a concern Theoretical contribution/Originality: This study provides insight into The fluctuations in the finance performs of Islamic banks using the RBBR approach, as well as contributing to understanding the stability of the Islamic banking sector in Indonesia. Practitioner/Policy Implications: Research This give outlook for the takers policies , regulators, and bank management regarding importance efficiency operational , management liquidity , as well as strengthening governance​ For ensure sustainability bank performance Research limitations: This research has limitations in the use of quantitative data which only covers the last four years, so it does not fully reflect long-term trends.